2018
DOI: 10.3390/bios8010008
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Biomimetic Material Made of Pyrrole for CA 15-3 and Its Application as Sensing Material in Ion-Selective Electrodes for Potentiometric Detection

Abstract: This work reports a very simple approach for creating a synthetic antibody against any protein of interest and its application in potentiometric transduction. The selected protein was Breast Cancer Antigen (CA 15-3), which is implicated in breast cancer disease and used to follow-up breast cancer patients during treatment. The new material with antibody-like properties was obtained by molecular-imprinting technology, prepared by electropolymerizing pyrrol (Py, 5.0 × 10−3 mol/L) around Breast Cancer Antigen (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The detection limit was 1.6 ng L −1 and the limit of quantification was 5.2 ng mL −1 . In addition, Santos et al [ 116 ] prepared a molecularly imprinted polymer using CA15-3 as a template by electropolymerizing pyrrol around CA15-3 on a fluorine doped tin oxide (FTO) conductive glass support to detect CA15-3. The detection of the concentration of the target was accomplished by potentiometric titration.…”
Section: New Strategies For Biosensormentioning
confidence: 99%
“…The detection limit was 1.6 ng L −1 and the limit of quantification was 5.2 ng mL −1 . In addition, Santos et al [ 116 ] prepared a molecularly imprinted polymer using CA15-3 as a template by electropolymerizing pyrrol around CA15-3 on a fluorine doped tin oxide (FTO) conductive glass support to detect CA15-3. The detection of the concentration of the target was accomplished by potentiometric titration.…”
Section: New Strategies For Biosensormentioning
confidence: 99%
“…However, with further studies, this new biosensor appears to have the potential for point-of-care use, as it has a wide concentration range that allows direct analysis of samples above or well below the cut-off value of 30 U/mL. Santos et al [ 54 ] also conducted a polymer to develop a sensor for CA15-3. Pyrrole was electropolymerised on a fluorine-doped tin oxide conductive glass.…”
Section: Mip Application For the Detection Of Cancer Biomarkersmentioning
confidence: 99%
“…171 An anti-body like ionophore layer was used as a carrier molecule between the solution and membrane in the potentiometric detection of CA 15-3 in serum. 172 Isildak et al showed that 4-hydroxybenzo-15-crown-5 ether can be used as ionophore in PVC membrane beryllium ISE for the detection of Be 2+ in solutions. 173 Enzymatic biocatalytic precipitation and nanogold labeling techniques have been used to improve the sensitivity in potentiometric immunosensors response.…”
Section: Electrochemical Nanosensorsmentioning
confidence: 99%